COMT gene variants and β-endorphin levels contribute to ethnic differences in experimental pain sensitivity - Xu, Feng; Yin, Jiangwen; Xiong, Erfeng; Wang, Ruixue; Zhai, Jinwen; Xie, Liping; Li, Yan; Qin, Xinlei; Wang, Erqiang; Zhang, Qingtong; Zuo, Yansong; Fan, Shiwen; et al. (Molecular pain, 2020)
This cross-sectional study investigated whether the catechol-O-methyltransferase (COMT) gene acts as a significant regulator of pain signaling pathways, regulates β-endorphin, and contributes to ethnic differences in pain sensitivity. One-hundred-sixty healthy subjects were enrolled in this study, with Han and Uyghur groups each consisting of 80 participants. Subjects went through six pain threshold experiments. From venous blood, COMT polymorphisms were genotyped, and serum β-endorphin levels were measured. Bivariate correlation analysis and multiple linear regression were used to identify the relationships among genotypes or β-endorphin levels and different types of pain thresholds. Han and Uyghur ethnic differences were determined in terms of acute-pressure pain-perception thresholds, blunt-pressure pain-perception thresholds, blunt-pressure pain-tolerance thresholds, electric pain-tolerance thresholds, β-endorphin levels, and distributions of rs4680 and rs4633 COMT polymorphisms. β-endorphin levels did not correlate with COMT rs4680 or rs4633 genotypes in both Han and Uyghur. Statistical predictors for a lower pain-threshold performance included being young, Uyghur, female, and having a low body mass index, low β-endorphin level, and the rs4680 GA or GG allele. There is the significant difference in pain sensitivity between healthy Han and Uyghur. COMT gene variants and β-endorphin levels contribute to ethnic differences in pain sensitivity.